Epigenome-wide methylation analysis shows phosphonoethylamine alleviates aberrant DNA methylation in NASH caused by Pcyt2 deficiency - Sophie Grapentine; Prasoon Agarwal; Vernon W. Dolinsky; Marica Bakovic (PLoS ONE, 2025)
Background Aberrant DNA methylation can lead to the onset of pathological phenotypes and is increasingly being implicated in age-related metabolic diseases. In our preceding study we show that the heterozygous ablation of Pcyt2, the rate limiting enzyme in phosphatidylethanolamine (PE) synthesis, causes an age-dependent development of non-alcoholic steatohepatitis (NASH), and that treatment with the Pcyt2 substrate phosphonoethylamine (PEA) can attenuate phenotypic NASH pathologies. Here, we hypothesize that abnormal DNA methylation patterns underly the development of Pcyt2 + /- NASH. In this study, we conduct an epigenome-wide methylation analysis to characterize the differential methylation of Pcyt2 + /- livers and investigate whether the attenuation of NASH with PEA treatment is associated with changes in DNA methylation. Results Pcyt2 + /- NASH liver experiences significant alterations in DNA methylation pattens relative to Pcyt2 + / + . Differentially methylated genes belong to pathways including PI3K-Akt signalling pathway, Foxo signalling pathway, oxidative phosphorylation and insulin signalling/secretion, indicating that epigenetic regulation underlies many of our previously established functional pathological mechanisms of Pcyt2 + /- NASH. Previously unidentified pathways during Pcyt2 deficiency are highlighted, such as cell cycle regulation and cellular senescence that may contribute to NASH development. Treatment with PEA dramatically attenuates aberrant total and protein-coding DNA methylation patterns by 96%. PEA treatment restored the methylation status of key genes involved in epigenetic modifications and induced differential methylation of genes associated with obesity and T2DM such as Adyc3, Celsr2, Fam63b. Conclusion The Pcyt2 + /- liver methylome and transcriptome is altered and likely underlies much of the pathology in Pcyt2 + /- NASH phenotype. The treatment with PEA significantly attenuates aberrant DNA methylation in Pcyt2 + /- liver and corrects the DNA methylation of genes involved in the pathogenesis of NASH, indicating its therapeutic potential. This analysis provides critical insight into the epigenetic basis of NASH pathophysiology and suggests diagnostic markers and therapeutic targets.